Flow Cytometric Analysis of Mediastinal Masses in Cats: A Retrospective Study - Bernardi, Serena; Martini, Valeria; Perfetto, Stefano; Cozzi, Marzia; Comazzi, Stefano (Frontiers in Veterinary Science, 2020)
Mediastinal masses occur in dogs and cats and are often investigated with cytology. However, discrimination between the two most common lesions (thymoma and lymphoma) may be challenging, especially when small/medium lymphocytes represent the prevalent population. The aim of the present study is to describe the flow cytometric aspects of mediastinal masses in cats and to assess the ability of flow cytometry (FC) to differentiate lymphoma from non-lymphomatous lesions. We retrospectively describe FC features of fine needle aspiration biopsies from cats with mediastinal masses. Cases were grouped in lymphoma and non-lymphoma based on results of cytology, histopathology, PCR for antigen receptor rearrangement (PARR) and follow-up. Scatter properties, positivities to CD5, CD4, CD8, CD21, CD18 and their co-expressions were recorded using a multicolour approach. Twenty cats were included, 12 lymphomas and 8 non-lymphomatous cases. Forward scatter (FSC) of lymphoid cells was higher in lymphoma group. Double positive CD4+CD8+ T-cells were the dominant population in 8 out of 12 lymphomas, whereas non-lymphomatous lesions showed no dominant lymphoid population in 5 out of 8 cases. Unlike dogs, the high prevalence of CD4+CD8+ lymphomas in cats makes difficult to differentiate lymphoma from non-lymphomatous lesions using FC alone. FC may add interesting information to refine diagnosis in some cases, but PARR and histopathology remain mandatory to solve differential in case of expansion of small-medium sized double positive lymphoid cells.